The role of demand response in mitigating market power: A quantitative analysis using a stochastic market equilibrium model - Mel T. Devine; Valentin Bertsch (The Economic and Social Research Institute (ESRI), 2019)
Market power is a dominant feature of many modern electricity markets with an oligopolistic structure, resulting in increased consumer cost. This work investigates how consumers, through demand response (DR), can mitigate against market power. Within DR, our analysis particularly focusses on the impacts of load shifting and self-generation. A stochastic mixed complementarity problem is presented to model an electricity market characterised by oligopoly with a competitive fringe. It incorporates both energy and capacity markets, multiple generating firms and different consumer types. The model is applied to a case study based on data for the Irish power system in 2025. The results demonstrate how DR can help consumers mitigate against the negative effects of market power and that load shifting and self-generation are competing technologies, whose effectivity against market power is similar for most consumers. We also find that DR does not necessarily reduce emissions in the presence of market power.
Keywords: C61; C79; Q41; Q48; Q49; 330; market power; demand response; load shifting; micro-generation